EFFECTS OF SYNCRETISM ON CHRISTIAN FAITH IN BUWANA PARISH IN LIGHT WITH COLOSSIANS 2:8: A CASE STUDY OF NGOMA ARCHDEACONRY, LUWERO DIOCESE - Amos Singa Twakira (Uganda Christian University, 2025)
This study investigated the effects of syncretism on the Christian faith within Buwana Parish, specifically in Ngoma Archdeaconry. It was guided by the specific objectives including: to analyze Colossians 2:8 in worship, to assess traditional beliefs and practices in Christian worship among Church members at Buwana Parish and to propose way forward for the church in addressing syncretism within the community in Buwana Parish. The study utilized a qualitative research approach and data was collected from a sample of 80 respondents using a research questionnaire and interview guide. The study findings asserted that the church plays a pivotal role in addressing the challenges of syncretism within the community. By understanding the complexities of cultural influences and doctrines. The analysis highlights the importance of fostering a strong biblical foundation, promoting discipleship, and engaging meaningfully with the community. Through education, open dialogue, and a commitment to spiritual growth, the church can effectively counteract the effects of syncretism and reinforce its identity as a distinct Christian community. By implementing the recommendations outlined above, the church can strengthen its witness and remain a beacon of hope and truth in a complex world. From the findings of the study, it was recommended that there is a need to enhance educational programs by developing comprehensive educational initiatives is essential for raising awareness about syncretism and its implications within the church community. Further recommendations included strengthening discipleship efforts which is crucial for fostering spiritual growth and maturity among congregants, and this can be achieved by implementing robust discipleship programs that focus on holistic development, fostering community engagement which is also essential for building strong relationships between the church and its surrounding community, and this can be achieved by creating platforms for open dialogue about cultural beliefs and practices. And finally, promoting cultural sensitivity which is a vital aspect for the church’s ability to connect meaningfully with diverse community members, and this begins with training church leaders and members to recognize and respect cultural practices that align with biblical teachings.
Undergraduate
Keywords: S; Syncretism